2019
DOI: 10.3233/ip-180107
|View full text |Cite
|
Sign up to set email alerts
|

The barriers to the opening of government data in the UK: A view from the bottom

Abstract: This paper explores some of the key barriers to Open Government Data (OGD) that responsible civil servants in the UK face as they try to comply with the UK-led OGD initiative. Empirically, we provide a quantitative analysis of the resources published on the government’s central OGD portal, data.gov.uk, and a unique insight into the publishing of OGD in the UK based on 22 interviews with responsible individuals at the operational level of publishing OGD. Our findings reveal that while the barriers to open gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In some cases, they are explicitly linked. For example, individual perspectives on the value of sharing data directly influence the extent to which they perceive institutional barriers (Wang et al, 2019). The themes identified are described through a human factors lens, but are related to the themes in reviews focused on institutional barriers (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, they are explicitly linked. For example, individual perspectives on the value of sharing data directly influence the extent to which they perceive institutional barriers (Wang et al, 2019). The themes identified are described through a human factors lens, but are related to the themes in reviews focused on institutional barriers (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…With the tasks not part of the formal incentive system in place, they are done ad hoc, if at all (Shao et al, 2019). Similarly, Wang et al (2019) found that immediate managers were not supportive, regardless of levels of support at senior levels of government.…”
Section: Perceived Costs Versus Perceived Valuementioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Saxena (2018a) investigated the OGD initiatives among six Middle Eastern countries, Cyprus, Turkey, Egypt, Iran, Lebanon, and Jordan. Research studies on OGDs either focused on a single country (e.g., Tang, et al, 2019;Wang, Shepherd, & Button, 2019;Wieczorkowski & Pawełoszek, 2018) or investigated multiple countries in one study (e.g., Yi, 2019;Nayek, 2018;Lourenço, 2015). As an example of a multi-country investigation, Ham, Koo, and Lee (2019) covered 13 countries from North America, Europe, Asia, South America, and Oceania.…”
Section: International Landscape Of Ogdmentioning
confidence: 99%
“…Examples of a single country study include Tang et al (2019) on the US states and capital cities' OGDs, Wang et al (2019) on the UK OGDs, and Wang, Chen, & Richards (2018) on the Chinese province-level OGDs.…”
Section: International Landscape Of Ogdmentioning
confidence: 99%